Unintended consequences of welfare cuts on children and adolescents - Christian Dustmann; Rasmus Landersø; Lars Højsgaard Andersen (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
This paper studies the effects of a large welfare benefit reduction on the children in the affected families. The welfare cut targeted adult refugees who received residency in Denmark, and it reduced their disposable income by 30 percent on average over the first five years. We show that children exposed to the welfare cut during preschool and school-age obtained lower GPAs, experienced reduced well-being and overall education levels, and suffered lower employment and earnings as adults. Children in their teens at exposure faced large increases in conviction probabilities for violent and property crimes.
Keywords: I24; I30; J10; K14; 330; Social assistance; welfare state; crime; education; inequality